2009
DOI: 10.1038/onc.2009.257
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenic protein 6: a member of a novel class of prognostic factors expressed by normal and malignant plasma cells inhibiting proliferation and angiogenesis

Abstract: Pathogenesis of multiple myeloma is associated with an aberrant expression of pro-proliferative, pro-angiogenic and bone-metabolism-modifying factors by malignant plasma cells. Given the frequently long time span from diagnosis of early-stage plasma cell dyscrasias to overt myeloma and the mostly low proliferation rate of malignant plasma cells, we hypothesize these to similarly express a novel class of inhibitory factors of potential prognostic relevance. Bone morphogenic proteins (BMPs) represent possible ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 45 publications
1
89
0
Order By: Relevance
“…[36,37] In supernatants of human myeloma cell lines and in BM plasma, low levels of BMP-6 were found using ELISA. [33] Another study found more BMP-2 in sera from multiple myeloma patients than in normal sera, but still at low levels (~ 60 pg/mL). [38] We found increased levels of BMP-9 in myeloma sera compared to normal sera.…”
Section: Expression Of Components Of the Bmp Signaling Pathwaymentioning
confidence: 98%
See 4 more Smart Citations
“…[36,37] In supernatants of human myeloma cell lines and in BM plasma, low levels of BMP-6 were found using ELISA. [33] Another study found more BMP-2 in sera from multiple myeloma patients than in normal sera, but still at low levels (~ 60 pg/mL). [38] We found increased levels of BMP-9 in myeloma sera compared to normal sera.…”
Section: Expression Of Components Of the Bmp Signaling Pathwaymentioning
confidence: 98%
“…[30][31][32][33][34] ALK6 (BMPR1B) is variably expressed. [31,35] The SMADs -1, -4 and -5 are also expressed, but not SMAD8.…”
Section: Expression Of Components Of the Bmp Signaling Pathwaymentioning
confidence: 99%
See 3 more Smart Citations